Metal Ionization in Sub-atmospheric Pressure MALDI Interface: A New Tool for Mass Spectrometry of Volatile Organic Compounds - Bednařík, Antonín; Prysiazhnyi, Vadym; Preisler, Jan (Analytical chemistry, 2021)
A novel approach for the analysis of volatile organic compounds (VOCs) based on chemical ionization by Au+ ions has been proposed. The ionization is carried out in a commercially available dual sub-atmospheric pressure MALDI/ESI interface without any modifications. The Au+ ions are generated by laser ablation of a gold nanolayer with the MALDI laser, and VOCs are infused via the ESI capillary. The ultrahigh resolving power and sub-ppm mass accuracy of the employed mass spectrometer allow straightforward identification of the formed ion-molecule complexes and other products of Au+ interactions with VOCs in the gas phase. The performance of the technique is demonstrated on the analysis of various classes of organic molecules, namely, alkanes, alkenes, alcohols, aldehydes, ketones, aromatic compounds, carboxylic acids, ethers, or organosulfur compounds, expanding the portfolio of currently available methods for the analysis of VOCs such as secondary electrospray ionization, proton-transfer reaction, and selected ion flow tube mass spectrometry.
Keywords: Atmospheric Pressure; hmotnostní spektrometrie s elektrosprejovou ionizací; spektrometrie hmotnostní - ionizace laserem za účasti matrice; těkavé organické sloučeniny; sloučeniny síry; atmosférický tlak; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Spectrometry, Mass, Electrospray Ionization; Sulfur Compounds; Volatile Organic Compounds